2022
DOI: 10.3390/microorganisms10050890
|View full text |Cite
|
Sign up to set email alerts
|

Proteome and Physiological Characterization of Halotolerant Nodule Endophytes: The Case of Rahnella aquatilis and Serratia plymuthica

Abstract: Bacterial endophytes were isolated from nodules of pea and fava bean. The strains were identified and characterized for plant beneficial activities (phosphate solubilization, synthesis of indole acetic acid and siderophores) and salt tolerance. Based on these data, four strains of Rahnella aquatilis and three strains of Serratia plymuthica were selected. To shed light on the mechanisms underlying salt tolerance, the proteome of the two most performant strains (Ra4 and Sp2) grown in the presence or not of salt … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…On the other hand, explanatory studies have emerged showing how halotolerant strain responds to salinity at the level of the proteome. ACC deaminase-producing S. plymuthica Sp2 was molecularly studied using a proteomic approach ( Novello et al, 2022 ). Overall, the study revealed that the levels of proteins involved in salt stress responses (4.4% NaCl) were increased, while the levels of proteins involved in metabolism and strand structure were decreased.…”
Section: Alleviation Of Salinity Stress In Plants By Serrat...mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, explanatory studies have emerged showing how halotolerant strain responds to salinity at the level of the proteome. ACC deaminase-producing S. plymuthica Sp2 was molecularly studied using a proteomic approach ( Novello et al, 2022 ). Overall, the study revealed that the levels of proteins involved in salt stress responses (4.4% NaCl) were increased, while the levels of proteins involved in metabolism and strand structure were decreased.…”
Section: Alleviation Of Salinity Stress In Plants By Serrat...mentioning
confidence: 99%
“…Overall, the study revealed that the levels of proteins involved in salt stress responses (4.4% NaCl) were increased, while the levels of proteins involved in metabolism and strand structure were decreased. The main proteins with increased expression in the Sp2 proteome were DsbA, ATP, Porin OmpA, Porin OmpC, and LpoB ( Novello et al, 2022 ).…”
Section: Alleviation Of Salinity Stress In Plants By Serrat...mentioning
confidence: 99%
“…Bacterial strain identification was performed using mass spectrometry MALDI (Matrix-Assisted Laser Desorption/Ionization) and TOF/TOF (UltrafleXtreme, Bruker, Billerica, MA, USA), as reported by Novello et al [21]. A fresh bacterial colony grown on TSA was spotted in triplicate on an MTP 384 target plate (Bruker Daltonics, Milan, Italy).…”
Section: Identification Of Bacterial Strainsmentioning
confidence: 99%
“…The minimal inhibitory concentration (MIC) of sodium chloride was determined by microplate assay, as reported by Novello et al [21]. In detail, NaCl (Fluka) was dissolved in Tryptic Soy Broth (TSB, Sigma, Burlington, MA, USA) until a concentration of 28.8%.…”
Section: Growth Temperature Assessment and Evaluation Of Salt Tolerancementioning
confidence: 99%
“…In the exoproteome of the halotolerant bacterium Tistlia consotensis grown at high salinity, proteins associated with osmosensing, exclusion of Na + and transport of compatible solutes, such as glycine betaine or proline are abundant ( Rubiano-Labrador et al, 2015 ). Similarly, the proteomic analysis of halotolerant nodule endophytes, Rahnella aquatilis strain Ra4 and Serratia plymuthica strain Sp2 identified that different trans-membrane ABC transporters (ATP-binding cassettes) were the most represented among the up-regulated proteins in response to salt stress ( Novello et al, 2022 ). Moreover, the proteome comparison of halotolerant bacterium Staphylococcus aureus under different osmotic stress conditions revealed the differentially expressed proteins (DEPs) involved in fatty acid synthesis, proline/glycine betaine biosynthesis and transportation, stress tolerance, cell wall biosynthesis, and the TCA cycle, which may contribute to the osmotic stress tolerance of S. aureus ( Ming et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%